Prospective assessment of the risk of postoperative pulmonary complications in patients submitted to upper abdominal surgery - Pereira, PereiraEanes Delgado Barros; Fernandes, Ana Luisa Godoy; Anção, Meide da Silva; Peres, Clóvis de Araújo; Atallah, Álvaro Nagib; Faresin, Sonia Maria (São Paulo Medical Journal, 1999)
OBJECTIVE: To investigate associations between preoperative variables and postoperative pulmonary complications (PPC) in elective upper abdominal surgery. DESIGN: Prospective clinical trial. SETTING: A tertiary university hospital. PATIENTS: 408 patients were prospectively analyzed during the preoperative period and followed up postoperatively for pulmonary complications. MEASUREMENTS: Patient characteristics, with clinical and physical evaluation, related diseases, smoking habits, and duration of surgery. Preoperative pulmonary function tests (PFT) were performed on 247 patients. RESULTS: The postoperative pulmonary complication rate was 14 percent. The significant predictors in univariate analyses of postoperative pulmonary complications were: age >50, smoking habits, presence of chronic pulmonary disease or respiratory symptoms at the time of evaluation, duration of surgery >210 minutes and comorbidity (p <0.04). In a logistic regression analysis, the statistically significant predictors were: presence of chronic pulmonary disease, surgery lasting >210 and comorbidity (p <0.009). CONCLUSIONS: There were three major clinical risk factors for pulmonary complications following upper abdominal surgery: chronic pulmonary disease, comorbidity, and surgery lasting more than 210 minutes. Those patients with three risk factors were three times more likely to develop a PPC compared to patients without any of these risk factors (p <0.001). PFT is indicated when there are uncertainties regarding the patient’s pulmonary status.